ANALISIS PENDAPATAN DAN KELAYAKAN FINANSIAL USAHATANI TANAMAN SELA DIANTARA KELAPA DI KABUPATEN MINAHASA PROPINSI SULAWESI UTARA - Kalaba, Yulianti (FAPETKAN UNTAD, 2005)
A study was done in the regency of Minahasa, North Sulawesi Province using survey method with purposive sampling, to find an intercropping pattern between coconut trees which provided the maximum added income. The sample as large as 120 were taken from Tombatu and Wori subdistrict. In Tombatu coconut + vanilla intercropping was found to be the best pattern providing added income as high as Rp. 11.612.400/ha/year. Different result was obtained in Wori where coconut + banana intercropping was the best with added income as much as Rp. 3.212.000/ha/year. Key words : Income, inter cropping, coconut.